Rendimiento académico y ansiedad en una estudiante de 21 años de la Carrera de Psicología de la Universidad Técnica de Babahoyo - Suarez Olea, Shirley Elizabeth (2023)
The current case study with the title "Academic Performance and Anxiety in a 21-Year-Old Psychology Student at Technical University of Babahoyo" aimed to Determine the influence of anxiety on the academic performance of a 21-year-old student majoring in Psychology at Technical University of Babahoyo. This was a qualitative study with a descriptive design, in which techniques such as interviews, clinical history, and psychometric tests were applied. The instruments used included open-ended questionnaires, clinical history model, Hamilton Anxiety Scale, Panic Attack Symptom Scale, and Social Skills Test. The research results demonstrate that anxiety is a central factor affecting the student's academic performance. Symptoms of anxiety, such as distress, worry, lack of concentration, and irritability, negatively influence her ability to cope with challenging academic situations, such as public speaking. In conclusion, the influence of anxiety on academic performance manifests in the student's difficulty in public speaking and in her ability to establish social relationships. Her anxiety leads her to avoid challenging academic and social situations, which paradoxically reinforces her anxiety symptoms and worsens her academic and emotional well-being.